Effect of rotation rates on dissolution behavior of lime in CaO-FetO-SiO2-MgO system - Jia, Cao; Mou, Qiqiang; Yu, Yue; Muvunyi, Rodrigue Armel; Zhang, Mengxu; Li, Jianli (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
For the converter steelmaking process, incompletely dissolved lime will exist in steel slag in the form of f-CaO, which reduces utilization rate of metallurgical slag and causes the waste of resources. It is extremely important to reduce the production of f-CaO in steel slag and promote the quick and sufficient dissolution of lime. This paper is based on the early and middle stages of the converter slag-forming route based on CaO component. The dissolution rate of lime in four different slags was measured by rotating rod method. The evolution behavior of the lime-slag interface and the change behavior of the lime dissolution rate were studied by X-ray diffractometer and electron probe micro-analyzer. The experimental results show that CaO-FeO solid solution and (Ca, Mg, Fe) olivine are formed when lime reacts with molten slag at 1400℃. When the FeO content decreases, CaO will react with the calcium-magnesia-silica to form a high melting point and dense 2CaO·SiO2 layer. In addition, at different rotation rates, a 3CaO·SiO2 phase layer is formed between CaO-FeO solid solution layer and C2S layer. When rotation rate increases, the dissolution rate of lime also increases and mass transfer coefficient reaches the maximum when rotation rate is 180 rpm. The maximum values are respectively 20.54×10-6 m/s, 7.86×10-6 m/s, 9.38×10-6 m/s, 5.53×10-6 m/s.